PENGEMBANGAN KOMPETENSI PEDAGOGICAL CONTENT KNOWLEDGE PADA MAHASISWA CALON GURU DALAM KEGIATAN MAGANG BERSERTIFIKAT KAMPUS MERDEKA DI GLOBAL ISLAMIC BOARDING SCHOOL YAYASAN HASNUR CENTRE - Dipa Suharto, - (LPPM Universitas Pendidikan Indonesia, 2022)
Pedagogical Content Knowledge (PCK) is one of the four competencies that must be mastered by a teacher. Mastery of PCK competencies is important because it can realize effective learning for students. Thus, student teacher candidates as prospective educators must of course begin to develop these competencies before having a career as a professional teacher. "Magang Bersertifikat Kampus Merdeka" is a student career competency development program organized by the Indonesian Ministry of Education and Culture. Collaborating with the Global Islamic Boarding School Yayasan Hasnur Centre, the Certified Apprentice program provides internships in the field of competency development for pre-service teacher students. The purpose of this study is to describe the competency development of pre-service teacher students in a certified internship program at the GIBS Hasnur Centre Foundation. This type of research is descriptive qualitative with data collection methods of observation, interviews, and documentation. The results of this study indicate that from the competency development process carried out, there is a development of Pedagogical Content Knowledge competence in pre-service teacher students after participating in the certified internship program at the Global Islamic Boarding School, Hasnur Centre Foundation